Research concerns of university librarians from Balti (Confluenţe Bibliologice, 2012)
The author describes the work of University Colloquia “Tradition and innovation in research”, the 2nd edition. The main librarian title in 2011 year was “Library and user dialog 2.0: innovation and information for all”. In 3 sections were presented 11 abstract papers and 3 tutorials. 55 librarians attended.Topics broached: the library impact on training future professionals, participatory management, promoting Open Access, human communication, ethics of serving the user 2. 0.
Keywords: Colloquia Professorum; scientific research